Correlation between admission hyperglycemia and postoperative pneumonia after hip fracture surgery: A propensity score-matched study - Yuanchao Luo; Xiaomin Ni; Wei Yao; Wei Wang; Yuhao Li; Qiaomei Lv; Wenbo Ding; Wanyun Tang (Scientific Reports, 2024)
Abstract The association between admission hyperglycemia and postoperative pneumonia is unclear in hip fracture patients. We investigated the relationship between admission hyperglycemia and postoperative pneumonia after hip fracture surgery. This retrospective study analyzed data from 1,267 geriatric patients admitted for hip fractures. Patients were categorized into normoglycemic (< 6.10 mmol/L) and hyperglycemic (≥ 6.10 mmol/L) groups based on admission blood glucose levels. Multivariable logistic regression and propensity score matching (PSM) were used to control for potential confounding variables and estimate adjusted odds ratios and 95% confidence intervals for postoperative pneumonia (POP). We also examined the dose-dependent link between admission blood glucose and the likelihood of developing POP. Further analyses evaluated whether admission hyperglycemia has differing impacts on POP outcomes among hip fracture patients without diabetes (NDM) versus those with diabetes (DM). Additionally, subgroup analyses were conducted to assess the influence of other factors on the relationship between admission blood glucose and POP occurrence. Patients with admission hyperglycemia had significantly higher rates of POP compared to normoglycemic patients, both before (13.2% vs. 4.8%) and after (10.1% vs. 5.8%) PSM. Admission hyperglycemia is an independent risk factor of POP (OR = 2.64, 95% CI: 1.42–4.92, p = 0.002). The association persisted after PSM(OR = 2.90, 95% CI: 1.35–3.86, p = 0.016). Additionally, higher blood glucose levels correlated with a greater likelihood of developing POP. A dose–response relationship was observed between blood glucose levels and the risk of POP. Non-diabetic group patients with hyperglycemia were at higher risk of POP than diabetic group patients with hyperglycemia. Finally, the relationship between hyperglycemia and increased POP risk is modulated and influenced by the ASA classification of the patient. Admission hyperglycemia is an independent risk factor for POP after hip fracture surgery in the elderly. There is a dose–response relationship between admission blood glucose and the occurrence of POP, which is more significant in non-diabetic patients than diabetic patients.